TRADISI TIBAN DI KECAMATAN TRENGGALEK DALAM PERSPEKTIF FIQH - Ihtiar, Habib Wahidatul (Ahkam: Jurnal Hukum Islam, 2016)
This study was conducted concerning the real condition in the societyindicating that people in Trenggalek still do Tiban ritual, which is notprescribed by Fiqh, to expect the coming of the rain after a long dryseason, in contrast to asking for the rain to Allah SWT. The focuses ofthis study are (1) why do the people in Trenggalek district still conductTiban ritual? (2) How do people in Trenggalek district practice Tibanritual? (3) How is Fiqh perspective towards Tiban ritual in Trenggalekdistrict? This study was qualitative research employing field researchdesign. To obtain valid and accurate data, the data collecting methodswere (1) Determining informants, (2) Observation, and (3) Deepinterview. The data were then analyzed by using interactive method.The results of this study were as the following; (1) There were threereasons why the people in Trenggalek district do Tiban tradition. Thefirst is due to a long dry season. The second is the believe of peoplethat Tiban tradition is the quicker way to ask for the rain, and the lastis that Tiban tradition is highly expected as a media to perpetuate theancient culture; (2) The practice of Tiban tradition consists of threesteps: opening step, action step, and closing step; (3) From Fiqhperspective, it can be said that Tiban is such a forbidden tradition.Kata kunci: Tradisi Tiban, Fiqh